Kendali Optimal Model LCS Pada Populasi Tanaman Padi Sawah Dari Serangan Hama Tikus Sawah Dan WBC Menggunakan Prinsip Minimum Pontryagin - Triwidodo, G; Ratianingsih, R; Nacong, N (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2020)
ABSTRACT Rice field plants (Oryza sativa) is one of the main food crop that very essential for common poeple. On the other hand, rice become as the main commodity of the common poeple. According to Badan Pusat Statistik ( BPS ) data, the consumption of it in 2011 reached 139 kg of due to 237 million of Indonesian resident. The cultivation of rice field production obstacle is the pest attack. The able prime pest that caused the rice production damage is field mouse pest (Rattus argintiventer) and rice stem pest (Nilaparvata Lugens). Both types have a very high reproduction rate. This research studies mathematically the damage of rice field plants population control at vegetative phase. That designed to minimize the number of vegetative rice population phase. A logistic Competing Species model is built to describe the interaction between both the pest at the vegetative phase rice growth. The Pontryagin minimum principles is used to determine the optimal control solution. The solution is solved from the state and co-state equation that stationery evaluated using the indexed performance with optimal control and . The research result of indicate that the optimal control just optimalize the vegetative rice phase damage while the pest is not optimalized yet. Keyword : Stability, Jacoby Matrix, Eigen Value, Pontryagin Minimum, Oryza Sativa, Rattus Argintivente, Nilaparvata Lugens